Should the Maximum Duration of Fixed-Term Contracts Increase in Recessions? Evidence from a Law Reform - Pedro S. Martins (Institute for the Study of Labor (IZA), 2016)
Fixed-term contracts (FTCs) may be an important tool to promote hirings and employment, particularly in recessions or when permanent contracts are costly. Therefore, it may be useful to let some of the legal parameters of FTCs (as well as those of other labour market institutions) vary systematically over the business cycle, namely increasing their flexibility during downturns. We evaluate this idea by examining the short-term effects of a new law introduced in Portugal, in the midst of a recession, which increased the maximum duration of FTCs from three to four and a half years. Our analysis is based on regression-discontinuity (and difference-in-differences) methods, applied to matched panel data. We find a considerable take up of this measure, as conversions to permanent contracts drop by 20%. Moreover, while we do not detect significant effects on employment status in the subsequent year, worker churning is reduced significantly, as mobility of eligible fixed-term workers to other firms drops by 10%.
Keywords: J23; J41; J63; 330; employment law; worker mobility; segmentation; counterfactual evaluation